2012
DOI: 10.2215/cjn.07650711
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Estimated GFR Decline in Patients with Type 2 Diabetes and Preserved Kidney Function

Abstract: SummaryBackground and objectives This study examined predictors of the annual decline in estimated GFR (eGFR) in patients with type 2 diabetes and preserved kidney function.Design, setting, participants, & measurements In a prospective, observational cohort study, 1682 individuals with type 2 diabetes and baseline eGFR $60 ml/min per 1.73 m 2 (as estimated by the Chronic Kidney Disease Epidemiology Collaboration equation) were followed for 10 years. Linear regression was used to estimate participants' changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
140
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(172 citation statements)
references
References 43 publications
28
140
4
Order By: Relevance
“…In our cohort of stable patients after MI, we found a yearly decline of kidney function of 2.0 ml/min per 1.73 m 2 in patients on placebo, a value similar to that observed in other older cohorts with cardiovascular disease or diabetes (4,20). Patients who increased their daily intake by an estimated 398 mg EPA-DHA (comparable with the recommended dietary allowance) for 40 months had a slower yearly decline of kidney function of 1.4 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 88%
“…In our cohort of stable patients after MI, we found a yearly decline of kidney function of 2.0 ml/min per 1.73 m 2 in patients on placebo, a value similar to that observed in other older cohorts with cardiovascular disease or diabetes (4,20). Patients who increased their daily intake by an estimated 398 mg EPA-DHA (comparable with the recommended dietary allowance) for 40 months had a slower yearly decline of kidney function of 1.4 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 88%
“…Urinary protein excretion at study initiation was also independently associated with annual Ccr declines. Proteinuria/albuminuria has been previously reported to accelerate the progression of type 2 DKD [6][7][8][9] and our result is thought to be consistent with previous reports. With regard to urinary protein excretion, proteinuria and albuminuria have been reported as major risk factors for the progression of type 2 DKD patients [14,15].…”
Section: Discussionsupporting
confidence: 94%
“…Thus far, several investigations of factors associated with kidney disease progression in type 2 diabetes have been reported. These studies have shown that age, HbA1c, insulin treatment, estimated glomerular filtration rate (eGFR) levels, systolic BP, hypertension, serum uric acid, serum albumin, hemoglobin, albuminuria, and proteinuria have significant relationships with the decline of renal function [6][7][8][9]. However, the nature of the relationship among the various factors and the decline of renal function varied from study to study, highlighting the need to better understand these associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Then, rapid eGFR decline, incidence of CKD, and incidence of albuminuria were modeled separately as a function of vitamin D at baseline using unconditional logistic regressions. Both eGFR and albuminuria have been previously associated with change in eGFR, rapid eGFR decline, and incident CKD (26,27). In the CoLaus study, the age-and sex-adjusted associations of baseline eGFR and albuminuria (independently of each other) with change in eGFR, rapid eGFR decline, and incident CKD were all highly significant (P,0.001); higher baseline eGFR was associated with greater eGFR loss, higher prevalence of rapid decline and lower CKD incidence; higher baseline albuminuria was associated with greater loss in eGFR, increased rapid decline, and greater CKD incidence.…”
Section: Statistical Analysesmentioning
confidence: 99%